Sample of intelligence, kindness, delicacy and tact ... - Вітковська, І. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
To the memory Andryshchenko. A.I.